In vitro Regeneration of a Vulnerable Medicinal Plant Hibiscus lobatus Kuntze. through Stem Callus Culture (Plant Tissue Culture and Biotechnology, 2025)
Hibiscus lobatus Kuntze., an endemic and vulnerable medicinal plant of the Western Ghats, is on the verge of threatening status due to habitat destruction, prolonged dormancy, uprooting and over-exploitation of its stems and roots for their medicinal value. This investigation established a reliable in vitro micropropagation protocol by culturing stem explants. 2,4-D was the most effective growth regulator in inducing a callogenic response from the excised end of the stem explants at the concentration of 1 mg/l. Subculturing the stem callus to the media supplemented with 1.25 mg/l 2,4-D induced rhizogenesis. The interaction of BAP (3.0 mg/l.) and TDZ (0.5 mg/l.) induced multiple shoot differentiation from the stem calli. Subculturing the caulogenic nodules to lower concentrations of BAP promoted the development of root-intact plantlets in a single-phase culture. The stem callus regenerants were successfully hardened and 78% of the plants were survived in field condition.Plant Tissue Cult. & Biotech. 34(2): 247-254, 2024 (December)